2006
DOI: 10.1007/s10641-006-9048-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on strontium:calcium ratios in the otoliths of the West African black-chinned tilapia Sarotherodon melanotheron in a hypersaline estuary

Abstract: The biology and the behaviour of fish populations in hypersaline environments are poorly known. The habitat occupation strategy of the tilapia Sarotherodon melanotheron has been studied along a salinity gradient in the Saloum hypersaline estuary in Senegal (salinity between 32 and 100). The individual migratory behaviour has been analysed from otolith strontium-to-calcium concentration ratios from fish sampled in five locations during the 2003 wet season and the 2004 dry season. In the upper part of the estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…Otolith Ba : Ca generally shows a negative relationship with salinity (Elsdon and Gillanders 2005a;Dorval et al 2007) and has been suggested as a tracer of salinity. Likewise, Sr : Ca has often been used as a tracer of salinity because of the positive relationship between otolith Sr : Ca and salinity (see review by Secor and Rooker 2000), although experimental laboratory studies report mixed results, which likely reflect underlying differences in water chemistry (Elsdon et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otolith Ba : Ca generally shows a negative relationship with salinity (Elsdon and Gillanders 2005a;Dorval et al 2007) and has been suggested as a tracer of salinity. Likewise, Sr : Ca has often been used as a tracer of salinity because of the positive relationship between otolith Sr : Ca and salinity (see review by Secor and Rooker 2000), although experimental laboratory studies report mixed results, which likely reflect underlying differences in water chemistry (Elsdon et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated stock structure of fish based on stable isotopes and/or Sr : Ca ratios in otoliths, including at sites that were slightly hypersaline (with a maximum salinity of between 42.5 and 65 [Dufour et al 1998;Edmonds et al 1999;Bastow et al 2002]). A single study has investigated the relationship between Sr : Ca ratios of otoliths and salinity for fish collected from Saloum estuary (Senegal, West Africa), where salinities ranged from 32 to 58 during the rainy season and from 40 to 100 during the dry season (Diouf et al 2006). Sr concentration in the water and its relationship to salinity was also investigated within the same estuary, but samples were collected 2 yr after the fish; therefore, no direct comparison could be made between otolith Sr : Ca and water Sr (Diouf et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of fish along estuaries can indicate the tolerable salinity range of different species (Cardona 2000;Diouf et al 2006;Bachman and Rand 2008;Macdonald and Crook 2010), however future changes in salinity may cause conditions to move towards, or away from the optimum conditions for each species (Labonne et al 2009). For example, large increases in salinity may have negative impacts on freshwater and estuarine resident species through physiological stress (Elliott et al 2007), particularly where upstream estuarine areas have become hypersaline Pratchett et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends have been observed in fishes living in adverse environmental conditions, as regards salinity, oxygen, food availability or predation pressure, and are interpreted as trade-offs in the context of life history strategies (mosquitofish Gambusia spp., Brown-Peterson and Peterson 1990; Alcaraz and García-Berthou 2007; Caspian roach Rutilus rutilus caspicus, Naddafi et al 2005; for cichlids: Chapman 2008, 2012;Russell et al 2012). Populations of S. m. heudelotii exhibit a marked genetic structure (Ndiaye 2012) and studies of their mobility indicate that this species is rather sedentary (Diouf et al 2006). Henceforth, it is uncertain whether the aforementioned variations in the life history traits of S. m. heudelotii in environments with contrasting salinities reflect genetic differences between populations or phenotypic plasticity in response to salinity or to associated environmental factors (food, predation, oxygen).…”
Section: Introductionmentioning
confidence: 99%